Reciprocal Influence of Liquidity and Capital Structure on Profitability in Electronic Retail Companies on the Indonesian Stock Exchange 2021-2023 - Wahyuni Sri Astutik; Kartika Piniji Dwi Budiarti; Diana Isnaeni; Yanto Budi Prasetya; Yani Dwi Restanti (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Profitability is the company's ability to earn profits in a certain period. Profitability can be used as a reference for investors when they want to make an investment, and is important information for other related parties. The company's profitability will be assessed as having good performance so that it can survive and compete. Companies that produce high profitability will be able to survive and have high competitiveness. For management, profitability is important information for making better and profitable decisions. Profitability is influenced by many variables, including capital structure and liquidity. The analysis of capital structure and liquidity in relation to profitability is a good thing if it is linked to strategic decision-making. Method: In this research, the data used is secondary data in the form of annual financial reports published on the IDX and the company's official website during the 2021-2023 period. The type of research used is explanatory research. The research carried out in this study used a quantitative approach. The population comprised 8 retail companies. The sampling technique was purposive sampling. The analysis technique used was descriptive statistical analysis, with data processing using Microsoft Excel and SPSS Version 21. Results: The findings show that liquidity significantly and positively affects profitability, with a t-test significance value of 0.031. Capital structure also has a significant positive effect on profitability, with a significance value of 0.030. Reciprocally, liquidity and profitability influence each other positively, where the effect of profitability on liquidity shows a t-test significance of 0.011. Conclusion: This study concludes that liquidity has a higher significance level than capital structure; therefore, companies should pay greater attention to liquidity because it contributes to increased profitability. Reciprocally, the effect of capital structure on profitability is significantly positive, but profitability does not affect capital structure, indicating that companies tend to rely on internal funding in line with the Pecking Order Theory.